Biostatistics Leader in Türkiye from the Eyes of His Students: Prof. Kadir Sümbüloğlu - Kul, Seval; Doğan, İlkay; Balat, Ayşe; Açıkgöz, Bektaş; Alparslan, Zeliha Nazan; Serçelik, Alper; Berhuni, Mustafa (European Journal of Therapeutics, 2024)
A correction to this article was published on 30/12/2024. The correction can be accessed via the following link; https://doi.org/10.58600/eurjther2587